Principali commenti medievali alla messa romana fino al XII secolo: autori e tipologia - Celiński, Łukasz (Warszawskie Studia Teologiczne, 2024)
In the 9th century, thanks to the work of Amalarius of Metz, a new type of liturgical source, known today as the allegorical commentary on the liturgy, was born. Although culturally and methodologically very distant from us, allegorical commentaries, in addition to witnessing the history of the method of interpreting the liturgy, are also valuable sources of the ritual structure of the Roman Mass after the Carolingian reform and before the creation of the complete missal in the 13th century. This paper offers a concise look at the main medieval commentaries on the Mass, compiled by the end of the 12th century, paying special attention to their authors as well as the type of Mass they described.